Identification of Differential Expression Genes in Leaves of Rice (Oryza sativa L.) in Response to Heat Stress by cDNA-AFLP Analysis. (17th February 2013) - Cao, Yunying; Zhang, Qian; Chen, Yanhong; Zhao, Hua; Lang, Youzhong; Yu, Chunmei; Yang, Jianchang
Abstract : High temperature impedes the growth and productivity of various crop species. To date, rice ( Oryza sativa L.) has not been exploited to understand the molecular basis of its abnormally high level of temperature tolerance. To identify transcripts induced by heat stress, twenty-day-old rice seedlings of different rice cultivars suffering from heat stress were treated at different times, and differential gene expression analyses in leaves were performed by cDNA-AFLP and further verified by real-time RT-PCR. In aggregate, more than three thousand different fragments were indentified, and 49 fragments were selected for the sequence and differential expressed genes were classified functionally into different groups. 6 of 49 fragments were measured by real-time RT-PCR. In addition, the variations of three different polyamine contents in response to heat stress through high-performance liquid chromatography (HPLC) analysis were also performed. The results and their direct and indirect relationships to heat stress tolerance mechanism were discussed.